Regression Analysis To Forecast Malaysia's Imports Of Crude Material - Rose Irnawaty Ibrahim; Mohamed A.Hmilad; Samiappanmarappan (Institute of Research and Journals, 2024)
International Journal of Management and Applied Science, ISSN: 2394-7926 Volume-1, Issue-4, May-2015